Contribution of annexin A1 to anticancer immunosurveillance - Baracco, Elisa Elena (Oncoimmunology, 2019)
Mouse cancers lacking the expression of annexin A1 (ANXA1) fail to respond to immunogenic chemotherapies. This has been initially explained by the requirement of extracellular ANXA1 (which is released from dying cancer cells) to engage formyl peptide receptor-1 (FPR1) on dendritic cells (DC) for the establishment of corpse/DC synapses. Here, we show that ANXA1-deficent cancer cells exhibit a defect in the exposure of calreticulin (CALR), which is an important “eat-me” signal, facilitating the phagocytic uptake of dead-cell antigens by DC. Of note, intratumoral injection of recombinant CALR protein was able to restore the therapeutic response of ANXA1-deficient cancers to anthracycline-based chemotherapy. Carcinomas developing in patients tend to downregulate ANXA1 expression as compared to their normal tissues of origin. ANXA1-low breast, colorectal, lung and kidney cancers are scarcely infiltrated by DC and cytotoxic T lymphocytes, supporting the idea that ANXA1 deficiency facilitates immune escape. We propose that such ANXA1-low cancers might be particularly suitable to local immunotherapy with CALR protein.